EVALUASI PROFESIONAL GURU MATA PELAJARAN PENDIDIKAN AGAMA ISLAM YANG TELAH TERSERTIFIKASI DI KABUPATEN MANOKWARI - Naki, Mohamad (Pascasarjana IAIN Sorong, 2025)
This study aims First; to analyze the involvement of Islamic Religious Education teachers in becoming certified professional teachers in Manokwari Regency. Second; To analyze the impact of Islamic Religious Education teacher certification in realizing professional teachers in Manokwari Regency This study is Qualitative Descriptive. The research approach is phenomenology and sociology. The sources of research data are primary and secondary. Data collection uses observation, interview, and documentation methods. Data processing and analysis are through data reduction, data presentation, and drawing conclusions.The results of the study show that First, the involvement of Islamic Religious Education teachers in realizing certified professional teachers in Manokwari Regency includes completeness of administrative documents, teacher competence, and involvement in teacher working groups and subject-teacher forums. Second, the impact of Islamic Religious Education teacher certification in realizing teacher professionalism in Manokwari Regency is the increase in the quality of education, the growth of teacher enthusiasm and motivation, and the improvement in teacher welfare.